2009
DOI: 10.1002/ijc.24633
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C alpha‐dependent signaling mediates endometrial cancer cell growth and tumorigenesis

Abstract: Endometrial cancer is the most common invasive gynecologic malignancy, yet molecular mechanisms and signaling pathways underlying its etiology and pathophysiology remain poorly characterized. We sought to define a functional role for the protein kinase C (PKC) isoform, PKCa, in an established cell model of endometrial adenocarcinoma. Ishikawa cells depleted of PKCa protein grew slower, formed fewer colonies in anchorage-independent growth assays and exhibited impaired xenograft tumor formation in nude mice. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 47 publications
2
37
0
1
Order By: Relevance
“…[19][20][21] Several evidences indicate PKCs as key regulators of critical cell cycle phases, including G 0 -G 1 /S transition and G 2 /M progression. [16][17][18]22 Among them, PKCα, already reported to be part of PLCβ1 signaling, 11,13,23 is known for its involvement in G 1 /S transition. 24 It has been demonstrated that, in intestinal epithelial cells, an anti-proliferative regulation of Cyclin D1 was modulated by PKCα signaling.…”
Section: Human Erythroleukemia Cells K562 Overexpressing Plcβ1mentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21] Several evidences indicate PKCs as key regulators of critical cell cycle phases, including G 0 -G 1 /S transition and G 2 /M progression. [16][17][18]22 Among them, PKCα, already reported to be part of PLCβ1 signaling, 11,13,23 is known for its involvement in G 1 /S transition. 24 It has been demonstrated that, in intestinal epithelial cells, an anti-proliferative regulation of Cyclin D1 was modulated by PKCα signaling.…”
Section: Human Erythroleukemia Cells K562 Overexpressing Plcβ1mentioning
confidence: 99%
“…28,29 In detail, cyclin inhibitors such as p21/Cip1 and p27/Kip1, known to be necessary for cell cycle progression, [30][31][32] are often targeted by PKCs. 22,28,29,33 Here, we aimed to investigate the proliferation of Figure 1. overexpression of both pLCβ1 isoforms specifically modulates cyclin D3 protein levels in proliferating K562 cells.…”
Section: Human Erythroleukemia Cells K562 Overexpressing Plcβ1mentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we examined the effects of EEA1 silencing upon the following: activation of PDK1, a well established kinase for Akt Thr-308 phosphorylation (48 -50); p38 MAPK, which was reported as a kinase upstream of Akt Ser-473 (51); and PKC-␣, which was recently established as an Akt regulator (24,52). We first examined whether these kinases are recruited to EEA1 endosomes in response to Ang II.…”
Section: Eea1 Is Required For Activation Of Akt Upstreammentioning
confidence: 99%
“…It is the third most common cancer in females after breast and ovarian cancer and carry a high death rate (Yang et al, 2011). Although a large number of women affected, the pathophysiological mechanisms is still largely unknown (Haughian et al, 2009).…”
Section: Introductionmentioning
confidence: 99%